2016
DOI: 10.1177/1747493016632238
|View full text |Cite
|
Sign up to set email alerts
|

A comparison between the MoCA and the MMSE visuoexecutive sub-tests in detecting abnormalities in TIA/stroke patients

Abstract: All three of the Montreal cognitive assessment visuoexecutive sub-tests detected more abnormalities than the mini-mental state examination pentagon copying and thus contributed to the over 10-fold superiority of Montreal cognitive assessment over the mini-mental state examination for detection of visuoexecutive dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 16 publications
0
25
0
Order By: Relevance
“…MMSE and MoCA are the two most common scales used to test cognitive impairment in various neurological dysfunctions, such as stroke and dementia [25,26]. MMSE was developed to assess cognitive dysfunction in Alzheimer’s disease, which is marked by difficulties in memory progress and language, and the scale is less frequently coupled with executive function, word-finding, and visual spatial ability deficits in early diagnosis [27].…”
Section: Discussionmentioning
confidence: 99%
“…MMSE and MoCA are the two most common scales used to test cognitive impairment in various neurological dysfunctions, such as stroke and dementia [25,26]. MMSE was developed to assess cognitive dysfunction in Alzheimer’s disease, which is marked by difficulties in memory progress and language, and the scale is less frequently coupled with executive function, word-finding, and visual spatial ability deficits in early diagnosis [27].…”
Section: Discussionmentioning
confidence: 99%
“…The MoCA has good psychometric properties and is a valid screening tool to detect post-stroke cognitive impairment [13]. Although a recent study [14] questioned the accuracy of the MoCA to assess attention and executive function by stroke lateralization, the majority of studies have shown the MoCA to be superior compared to other screening measures such as the MMSE [11, 15, 16]. While primarily considered a screening tool, the MoCA has been used as a cognitive outcome measure in longitudinal studies where lengthy neuropsychological testing is not often feasible.…”
Section: Assessmentmentioning
confidence: 99%
“…Our findings also highlight the differences between two extensively used screening tests of global cognition, that is, MMSE and 11,17,18,20,28 The studies reported that the relative performance of MMSE and MoCA depends on the type/degree of cognitive impairment aimed to be detected. 11,12,18,28 In our study, the stroke survivors had a higher educational level than the controls, possibly because of slightly different geographical uptake areas.…”
Section: Discussionmentioning
confidence: 65%
“…When adjusting for this, the odds of having severe cognitive impairment defined as MMSE<23 were 2.5 times higher among the stroke survivors as compared to the controls. 20 We also noted that the MMSE word recall subtest scoring of the controls was surprisingly low (Table S2). 8,9 We further found that 10-year stroke survivors performed worse on the MMSE visuoconstruction subtest compared to controls, suggesting a higher prevalence of visuoexecutive deficits.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation